1961
DOI: 10.1084/jem.114.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytological Effects of Varied Inocula of Influenza Virus

Abstract: Variation in the amount and quality of influenza virus injected into the amniotic sac of the chick embryo led to differences not only in the yield of virus but also in the immunofluorescent cytology of the infection. The production of infectious virus was associated with a predominance of cells in which the virus antigens were first detected along the cell surface in contact with the amniotic fluid, later deeper in the cytoplasm, and finally, though to a lesser extent, in the nucleus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1968
1968

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Moffat et al (1960), Hillis et al (1960) and Watson (1961) reported alterations in the site and amount of influenza antigens when multiplicities of infection were altered. Accordingly, virus was diluted to give a ratio of one EID 50 per 104"° cells.…”
Section: Effect Of Multiplicity In Bkh21 Cellsmentioning
confidence: 99%
“…Moffat et al (1960), Hillis et al (1960) and Watson (1961) reported alterations in the site and amount of influenza antigens when multiplicities of infection were altered. Accordingly, virus was diluted to give a ratio of one EID 50 per 104"° cells.…”
Section: Effect Of Multiplicity In Bkh21 Cellsmentioning
confidence: 99%